Preprint manuscripts and servers in the era of coronavirus disease 2019. Issue 1 (23rd October 2020) - Nabavi Nouri, Shayan; Cohen, Yosef A.; Madhavan, Mahesh V.; Slomka, Piotr J.; Iskandrian, Ami E.; Einstein, Andrew J.
Abstract: Rationale, Aims, and Objectives: To both examine the impact of preprint publishing on health sciences research and survey popular preprint servers amidst the current coronavirus disease 2019 (COVID‐19) pandemic. Methods: The authors queried three biomedical databases (MEDLINE, Web of Science, and Google Scholar) and two preprint servers (MedRxiv and SSRN) to identify literature pertaining to preprints. Additionally, they evaluated 12 preprint servers featuring COVID‐19 research through sample submission of six manuscripts. Results: The realm of health sciences research has seen a dramatic increase in the presence and importance of preprint publications. By posting manuscripts on preprint servers, researchers are able to immediately communicate their findings, thereby facilitating prompt feedback and promoting collaboration. In doing so, they may also reduce publication bias and improve methodological transparency. However, by circumventing the peer‐review process, academia incurs the risk of disseminating erroneous or misinterpreted data and suffering the downstream consequences. Never have these issues been better highlighted than during the ongoing COVID‐19 pandemic. Researchers have flooded the literature with preprint publications as stopgaps to meet the desperate need for knowledge about the disease. These unreviewed articles initially outnumbered those published in conventional journals and helped steer the mainstream scientific community at the start of the pandemic. In surveying select preprint servers, the authors discovered varying usability, review practices, and acceptance polices. Conclusion: While vital in the rapid dispensation of science, preprint manuscripts promulgate their conclusions without peer review and possess the capacity to misinform. Undoubtedly part of the future of science, conscientious consumers will need to appreciate not only their utility, but also their limitations.